DIGITAL CUSTOMER JOURNEY: BUILDING CUSTOMER LOYALTY IN THE VIRTUAL WORLD - Loso Judijanto (CV. ADIBA AISHA AMIRA, 2025)
The digital customer journey is the process of customer interaction with a brand across various digital platforms, from awareness to post-purchase. This process has become increasingly important in the digital age as customers often move between interconnected online channels. To build customer loyalty, companies need to understand this digital journey and create consistent, relevant, and personalised experiences. Strategies such as data analytics, loyalty programme development, and omnichannel service implementation play an important role in strengthening customer relationships. In addition, technological evolutions such as artificial intelligence (AI) and automation provide new opportunities for more effective and efficient interactions. However, companies must also remain focused on a human-centric approach to ensure that emotional customer engagement is maintained. By adapting to changing technological trends and customer needs, companies can build sustainable customer loyalty in the digital world.